Monte Carlo study of the relative role of energy absorption mechanisms in solid disordered neon under irradiation with photons in the energy range of 4 to 800 Ry. (June 2020) - Kochur, A.G.; Chaynikov, A.P.; Yavna, V.A.
Abstract: Mechanisms of energy absorption in solid disordered neon under 4 to 800 Ry photon irradiation are studied by Monte Carlo simulation with accounting for the cascade decays of vacancies produced by primary and secondary ionization processes. The dominating channel for the transfer of energy to the sample giving about 55% of total absorbed energy is through ionization and excitation of atoms of the medium by secondary electrons produced by primary photoionization and secondary inelastic processes, and by vacancy decay cascades. The portion of energy absorbed in the acts of primary photoionization is significant only at incident photon energies fewer than 10 Ry, it is about 5% at incident photon energy near the Ne1s ionization threshold, and decreases rapidly at higher photon energies. The energy absorbed in secondary photoionization processes makes 3–5% of total absorbed energy on the whole incident photon energy interval. About 40% of total absorbed energy is transferred by low-energy electrons and photons that cannot ionize or excite atomic electrons. In the problems of radiation cancer therapy, at high energies of incident photons, the low-energy electrons produced in great quantities may contribute to DNA strand breaks via dissociative electron attachment. Highlights: Energy absorption in photon irradiated solid Ne is studied by Monte Carlo method. Ionization/excitation by secondary photons is the main channel of energy absorption. Cascade decay is a crucial factor in ionizing radiation effect on matter.